Restoring Public Trust through Ethical Leadership and Accountability Frameworks in Governance - Satia, Riban (Politeia : Journal of Public Administration and Political Science and International Relations, 2024)
This narrative review examines leadership, public ethics, and accountability frameworks in government institutions, aiming to synthesize current evidence and highlight research gaps. Literature was sourced from Scopus, Web of Science, JSTOR, and Google Scholar using keywords such as ethical leadership, public sector ethics, and accountability frameworks. Studies from the past decade were prioritized, covering both qualitative and quantitative evidence. Findings indicate that ethical leadership fosters integrity, strengthens accountability, and enhances public trust by modeling values that shape ethical organizational cultures (Demir et al., 2023; Wright et al., 2016). Accountability mechanisms—compliance-based, integrity-driven, and hybrid—are most effective when supported by political will, robust regulation, and participatory governance (Reddick et al., 2024; Sebastián et al., 2023). Organizational culture plays a central role in shaping ethical behavior, while gender diversity in leadership promotes inclusivity and public confidence (Mousa et al., 2021; Bastani et al., 2020). Despite these insights, research is constrained by reliance on case studies, self-reported measures, and limited comparative analysis. Political and cultural contexts significantly influence the effectiveness of ethics and accountability policies, yet cross-country and longitudinal studies remain scarce. The review concludes that integrating ethical leadership, accountability frameworks, organizational culture, and gender diversity is vital for resilient governance. Strengthening these areas can restore public trust, reinforce institutional legitimacy, and provide a foundation for sustainable and ethical governance in diverse contexts.